Entry to 2-aminoprolines via electrochemical decarboxylative amidation of N‑acetylamino malonic acid monoesters - Koleda, Olesja; Sadauskis, Janis; Antonenko, Darja; Treijs, Edvards Janis; Steberis, Raivis Davis; Suna, Edgars (Beilstein Journal of Organic Chemistry, 2025)
The electrochemical synthesis of 2-aminoprolines based on anodic decarboxylation–intramolecular amidation of readily available N-acetylamino malonic acid monoesters is reported. The decarboxylative amidation under Hofer–Moest reaction conditions proceeds in an undivided cell under constant current conditions in aqueous acetonitrile and provides access to N-sulfonyl, N-benzoyl, and N-Boc-protected 2-aminoproline derivatives.
Keywords: anodic oxidation; decarboxylation; electrosynthesis; Hofer–Moest reaction; non-proteinogenic amino acids